The financial aid of the Central Bank of Iraq to the government and its reflection on indicators of banking stability/ Applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to define the images of financial aid that it provides within their tasks (central banks to governments) and how it can affect the indicators of banking stability, as well as monitoring the levels of banking stability in the Iraqi economy through the indicators used by the Central Bank of Iraq, and the importance of research in banking stability lies in Iraq, because any decrease in the movement of the aggregate banking stability index will reflect negatively on the financial sector in Iraq. Therefore, the Central Bank sought to provide financial aid to the government through a group of components, some of which are represented by initiatives that contribute to revitalizing the national economy and the other help is to re-discount treasury transfers Reducing the exchange rate, which aims to support the general budget of countries for   the contribution of these components to achieving relative stability in the Iraqi banking sector.             The research hypothesis is based on the Central Bank of Iraq contributing to achieving stability in the banking sector by providing financial aid to the government. The researcher used one of the financial aid components, which is represented in development initiatives. The research used the historical method of a time series for the research variables, where it used the quantitative analytical method, which is the growth rates of the initiatives granted by the Central Bank of Iraq to a sample of specialized banks and the Housing Fund. In addition, the researcher used the financial ratios of the indicators of banking stability and the aggregate indicator. The research reached a set of results, the most important of which was the rise and fall of the aggregate index of banking stability in Iraq during the research period (2015-2020), and this may expose the banking sector to a risk when financial crises emerge, and it was also noted that one of the most important components of financial aid for the government is the initiatives of the Central Bank. The Iraqi Bank, which is of great importance and is linked to banking stability, and its impact on the profitability index of the banking sector. The research concluded that banking stability in Iraq is fragile and also showed that there is a relationship between banking stability and the initiatives launched by the Central Bank of Iraq to finance small and medium enterprises. And also maintaining banking stability, as it represents the largest part of the stability of financial institutions in general.